2016
DOI: 10.1038/srep36078
|View full text |Cite
|
Sign up to set email alerts
|

A Carbonaceous Membrane based on a Polymer of Intrinsic Microporosity (PIM-1) for Water Treatment

Abstract: As insufficient access to clean water is expected to become worse in the near future, water purification is becoming increasingly important. Membrane filtration is the most promising technologies to produce clean water from contaminated water. Although there have been many studies to prepare highly water-permeable carbon-based membranes by utilizing frictionless water flow inside the carbonaceous pores, the carbon-based membranes still suffer from several issues, such as high cost and complicated fabrication a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 65 publications
1
25
0
Order By: Relevance
“…The mechanism found in this article provides a clear microscopic understanding of the coupling between sorption and swelling in soft porous matter that goes well beyond wood and other cellulose-based materials. In particular, other soft porous materials such as kerogen in gas shale 37 , 38 but also man-made materials such as water artificial nanochannels 39 and polymer with intrinsic microporosity 40 are expected to display the same sorption/mechanical behavior. Extrapolation to wood should be made with caution as wood is a far more complex material than amorphous cellulose.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism found in this article provides a clear microscopic understanding of the coupling between sorption and swelling in soft porous matter that goes well beyond wood and other cellulose-based materials. In particular, other soft porous materials such as kerogen in gas shale 37 , 38 but also man-made materials such as water artificial nanochannels 39 and polymer with intrinsic microporosity 40 are expected to display the same sorption/mechanical behavior. Extrapolation to wood should be made with caution as wood is a far more complex material than amorphous cellulose.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the rigid molecular structure, the size range of the resulting plat-inum nanoparticles was uniform and the surface of platinum was "free" of capping agents, and although encapsulated, immediately highly reactive in electrocatalysis without further pre-treatments. In another recent study on PIM carbonization, Kim et al [33] have shown that also the prototypical polymer of intrinsic microporosity PIM-1 [34] can be carbonized (at 1100-1300 • C) to give thin microporous carbon membranes with improved ion rejection and flux properties for water purification under reverse osmosis condi-tions. Indeed, water flux and good salt rejection were reported to be better than those for current state-of-the-art water purification membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Their unique structural features and properties make them suitable for devices such as organic light emitting diodes (OLEDs) and sensors, [2][3][4] and for the production of membranes 5 for gas separations, 6,7 pervaporation, 8,9 and nanofiltration. 10 Further applications in water treatment, [11][12][13] gas storage, [14][15][16] and electrochemical devices have also been suggested. [17][18][19][20][21][22][23] In addition to the twisted chain structure of PIMs achieved by introducing sites of contortion, such as the spiro-centers of PIM-1, 5 they possess limited freedom of motion arising from prohibited rotation along the polymer backbone for instance via fused-ring structures.…”
mentioning
confidence: 99%